Immobilization of metal oxide particles via thin films generated through spin coating - Wong, Chong Hui (2019)
Janus particles are particles with multiple types of surface composition. Research in such particles has garnered considerable interest in recent years due to their unique properties and applications. One of the main strategies used in the fabrication of Janus particles is by surface modification. In this project, amphiphilic-amphiphobic Janus particles are fabricated through a surface modification process. Fluoroalkylsilane-titanium dioxide (FAS-TiO2) particles are initially immobilized onto a glass substrate through spin coating, followed by modification via ultraviolet irradiation on one side of the FAS-TiO2 particle. The influence of various spin coating parameters such as the spin speed, acceleration, spin duration, solution loading quantity of FAS-TiO2 methanol, FAS-TiO2 methanol concentration and surface treatment are studied to optimize the surface coverage and the uniform monolayer thickness of the thin film. A relatively uniform FAS-TiO2 monolayer thin film with good surface coverage of 43.25% was achieved by optimizing the parameters. After the spin coating process, the FAS-TiO2 thin film was irradiated with ultraviolet (UV) rays to produce the dual property particle. The resulting Janus particles were subsequently characterized by scanning electron microscope and contact angle analysis. The average contact angle of the fabricated amphiphilic-amphiphobic Janus particle with deionized water was found to be 129.68°.